(untitled) (Jurnal Manajemen Bisnis, 2026)
Sustainable entrepreneurship has become increasingly urgent in addressing environmental and social challenges, yet gender-specific dynamics in entrepreneurial marketing remain understudied. Understanding how women entrepreneurs apply entrepreneurial marketing is essential to strengthening inclusive and sustainable business ecosystems. This study examines the role of entrepreneurial marketing in improving sustainable business performance from a gender perspective. Using a quantitative survey approach, data were collected from 150 women entrepreneurs in Semarang who have managed environmentally friendly businesses for at least 3 years. Respondents were selected through purposive sampling, and data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that innovativeness, opportunity focus, and acceptable risk positively influence sustainability performance, highlighting women entrepreneurs’ emphasis on social value creation, adaptability, and measured risk-taking. However, proactivity, resource leveraging, and networking show no significant impact, reflecting structural barriers, differences in strategic orientation, and networking limitations that women entrepreneurs often face. This study provides novelty by uncovering gender-specific patterns in entrepreneurial marketing and their implications for sustainability outcomes. Theoretically, it advances the discourse on gender and entrepreneurship, while, in practice, it emphasizes the need for gender-sensitive policies, entrepreneurial training, and supportive ecosystems to enhance sustainable business performance.